Evaluación de la concentración de Mercurio (Hg) en agua y peces del río Mira. parroquia Lita - Pabón Paspuezán, Sofia Lisbeth (2024)
In Ecuador, mining activities pose a source of contamination to water sources due to the release of heavy metals into nearby rivers, which can enter animals such as fish through the digestive tract. This research aimed to assess mercury (Hg) pollution levels in both fish and water from the Mira River in the Lita parish, considering its significant mining activity and the use of its water for irrigation, with the fish being consumed by the local population. The methodology employed was descriptive-quantitative, utilizing non-probabilistic sampling based on the researcher's criteria, involving 150 fishermen who are actively engaged in fishing. Three communities were identified, with each considered a sampling point, resulting in a total of 18 samples for both water and fish. Water samples followed the guidelines of the NTE 2176 standard, while fish samples adhered to the Ecuadorian Technical Standard NTE-INEN 183:2013. Mercury concentration was determined using atomic absorption spectrophotometry with a hydride generator, employing the EPA 245.1 method for water and the AOAC 977.15 method for fish. The results revealed that the most captured and consumed fish species was the Sábalo, representing 33% of responses, followed by the Sabaleta (21%), collectively constituting more than 50% of the sample. Regarding the concentration of mercury in the tissue of the Sábalo fish, it was found that the levels did not exceed 0.5 mg/kg in accordance with the NTE-INEN 183:2013 standard.